The Influence of the Marketing Mix on E-loyalty for N’Pure Products on TikTok Shop in Greater Bandung - Zahra Aliya Hafizhoh; Hariyadi Triwahyu Putra (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The purpose of this study is to investigate how the marketing mix affects e-loyalty for N'Pure items on TikTok Shop in the Greater Bandung region. The study focuses on consumers who have purchased or used N’Pure products on TikTok Shop in the Greater Bandung area. This research employs a quantitative method, using an online survey to collect a sample of 140 respondents. In addition, the data analysis methods used in this study included multiple regression analysis, which was conducted using the Statistical Program for the Social Sciences (SPSS). Based on the findings of this study, online loyalty is positively and significantly influenced by three aspects of the marketing mix product, price, place, and promotion while online loyalty is negatively and significantly influenced by one aspect of the marketing mix. E-loyalty is influenced simultaneously by the marketing mix (product, price, place, and promotion). These results suggest that managers should routinely evaluate packaging design to prevent visual fatigue and implement dynamic pricing in line with digital purchasing trends.